A Safety Risk Management Approach Using Human Factor Analysis and Classification System (HFACS) Based Investigation for Urban Railway Maintenance Accidents - Ruslan, Rumaizah; Zulkifle, Nurfarizzatul Hana; Abdul Hamid, Nor Aziati; Sahak, Nurrul Hafeezah; Abdul Samad, Nurul Izzah (Journal of Technology Management and Business, 2025)
Despite the growth and modernization of the Malaysian railway industry, human factors remain a primary cause of workplace accidents. This research explores the human factors contributing to workplace accidents among maintenance workers in Malaysia's urban railway sector using the Human Factors Analysis and Classification System (HFACS). The research employs qualitative methods, including interviews with five maintenance workers who have experienced workplace incidents, along with a comprehensive review of 14 accident reports from 2017 to 2021. Findings reveal that unsafe acts are significant contributors to accidents, accounting for 28.6% of reported cases. These errors are often caused by distractions due to internal factors, such as excessive work pressure, or external factors, such as environmental disturbances. Preconditions for unsafe acts, including hazardous physical environments, emerged as the most frequent cause, representing 50% of cases. Other contributing factors include improper tool use (7.1%) and deficiencies in communication, coordination, and planning during routine maintenance tasks (14.3%). The findings from the interview session indicate that most workplace accidents were linked to unsafe acts, with 80% of respondents highlighting these as major causes. Respondents also identified preconditions such as physical environment, mental and physical states, and sensory misperception, in which 20% cited poor lighting, confined spaces, fatigue, and misreading instruments as key factors. Though supervisory issues were rarely mentioned, 20% of respondents blamed organisational shortcomings, such as lack of essential tools and poor resource management, for contributing to unsafe conditions. Preventive measures, such as wearing personal protective equipment (PPE) and fostering team-based monitoring in high-risk environments, were emphasised by respondents. This research accentuates the importance of applying the HFACS framework as a diagnostic tool, human-related contributing factors to railway maintenance accidents can be systematically identified, enabling the development of targeted interventions to enhance safety and reduce workplace incidents in railway maintenance operations.